Understanding Employees Intention to Stay or Leave: The Interplay of Financial Compensation, Workload, and Job Satisfaction - Laila Shofia Ningsih; Kertati Sumekar; Mulyanto Mulyanto (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the effects of financial compensation and workload on turnover intention, with job satisfaction serving as a mediating variable. The variables examined include financial compensation, workload, job satisfaction, and turnover intention. A quantitative approach with an associative research design was employed to empirically test the relationships and causal effects among these variables. The population consisted of all employees of PT Samwon Busana Indonesia Jepara. A total of 210 respondents were selected as the research sample using the Isaac and Michael formula at a 5% margin of error and were chosen through a simple random sampling technique. Data were collected through an online questionnaire distributed via Google Forms. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS version 3.0. The findings indicate that financial compensation has a negative and significant effect on turnover intention, whereas workload has a positive and significant effect on turnover intention. Furthermore, financial compensation positively and significantly influences job satisfaction, while workload negatively and significantly affects job satisfaction. Job satisfaction also demonstrates a negative and significant effect on turnover intention, confirming its role in reducing employees’ intention to leave the organization.